MERGERS AND ACQUISITIONS: A REVIEW OF EPISODE, FAILURE AND SUCCESS NEW MANTRA - Muninarayanappa; Augustin Amaladas (European Scientific Journal, ESJ, 2013)
Collaborations, strategic alliances, powerful partnerships will strengthen the economy. Encouragements from Governments through legislations and tax concessions will further strengthen mergers and acquisitions. This study focuses on factors for the failure of mergers and acquisitions globally and more particularly in India and to review the success mantra for effective implementation of mergers and acquisitions. This research paper is conceptual in nature. The studies undertaken guide the management and persons involved not to fail to understand the reasons for pre and post merger failures. Understanding culture, training of managers to develop change agents, communication to stake holders, building targets, developing a new culture, leader to lead, careful planning and implementation at each stage of mergers make merger successful.